The Relationship Between Use of Active Learning Methods and Parental Involvement Learning on Student Achievement - Sholeh, Muh Ibnu; Singh, W C; Nashihudin, Moh; Sokip, Sokip; Syafii, Asrop; ‘Azah, Nur; Sahri, Sahri; Muzakki, Hawwin; Wahruddin, Bambang (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
Abstract This study aims to investigate the relationship between the use of active learning methods and parental involvement in learning on student achievement at MAN 1 Tulungagung. Effective implementation of both factors could be a vital strategy in enhancing the quality of Islamic religious education and student achievement. Data were collected through questionnaires distributed to 74 teachers. The sampling technique employed the Isaac and Michael table with a 5% error rate, resulting in 62 samples from the total population. The data collection instrument was a Guttman scale questionnaire. Data analysis included validity and reliability tests, as well as linear and multiple regression analyses using SPSS software. The research findings indicate that the use of active learning methods significantly influences student achievement, with a beta coefficient of 0.42 and a t-value of 8.40 (p-value < 0.001). Parental involvement in religious education also significantly affects student achievement, with a beta coefficient of 0.38 and a t-value of 6.54 (p-value < 0.001). The combined use of active learning methods and parental involvement significantly impacts student achievement. Active learning methods have a beta coefficient of 0.35, while parental involvement in religious education has a beta coefficient of 0.28. Both variables show high significance (p-value < 0.001). This study contributes significantly to understanding the factors influencing student achievement in the context of Islamic religious education. Future research could explore diverse teaching methods, parental roles, and improved methods of measuring student achievement. Keywords: Learning Methods, Parental involvement, Student Achievement.